2020
DOI: 10.3390/biom10040546
|View full text |Cite
|
Sign up to set email alerts
|

Ranunculus bulumei Methanol Extract Exerts Anti-Inflammatory Activity by Targeting Src/Syk in NF-κB Signaling

Abstract: 1) Background: Ranunculus bulumei is a flowering plant that belongs to the Ranunculus species. Several Ranunculus species, such as R. aquatilis and R. muricatus, have traditionally been used to treat fever and rheumatism throughout Asia, suggesting that plants belonging to the Ranunculus species may have anti-inflammatory effects. To our knowledge, the pharmacological activity of R. bulumei has not been reported. Therefore, in this study, we aim to assess the anti-inflammatory activity of a methanol extract th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…Besides NF-κB and AP-1 subunits, other upstream signaling proteins have been identified that are involved in the NF-κB and AP-1 pathways, including IκBα and PI3K p85 or MAPKs and MAPKKs, respectively. In agreement with another report [ 21 ], the IκBα and p-IκBα bands were not regularly detected at 15 min due to the degradation, while rapid recovery of the protein at 30 min after LPS stimulation was observed [ 22 ]. Since Cs-EE regulated IκBα at 5 min, we examined whole-cell lysates from LPS-stimulated RAW264.7 cells or primary peritoneal macrophages at earlier time points.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Besides NF-κB and AP-1 subunits, other upstream signaling proteins have been identified that are involved in the NF-κB and AP-1 pathways, including IκBα and PI3K p85 or MAPKs and MAPKKs, respectively. In agreement with another report [ 21 ], the IκBα and p-IκBα bands were not regularly detected at 15 min due to the degradation, while rapid recovery of the protein at 30 min after LPS stimulation was observed [ 22 ]. Since Cs-EE regulated IκBα at 5 min, we examined whole-cell lysates from LPS-stimulated RAW264.7 cells or primary peritoneal macrophages at earlier time points.…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies have demonstrated that Src has a crucial role in activating immune cells and is part of upstream signaling enzymes that mediate transcriptional activation of NF-κB via phosphorylation of PI3K p85 then IKK to degrade IκBα. Indeed, anti-inflammatory remedies derived from compounds or plant extracts that target Src have been shown to diminish inflammatory responses via a blockade of NF-κB pathways [ 10 , 11 , 22 ]. Furthermore, Cs-EE inhibited activation of two MAPKs, JNK and ERK.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations